SMART FABRICS-WEARABLE TECHNOLOGY - Chika, Yinka-Banjo; Adekunle, Salau Abiola (International Journal of Engineering Technologies and Management Research, 2017)
Smart fabrics, generally regarded as smart Textiles are fabrics that have embedded electronics and interconnections woven into them, resulting in physical flexibility that is not achievable with other known electronic manufacturing techniques. Interconnections and components are intrinsic to the fabric therefore are not visible and less susceptible of getting tangled by surrounding objects. Smart fabrics can also more easily adapt to quick changes in the sensing and computational requirements of any specific application, this feature being useful for power management and context awareness. For electronic systems to be part of our day-to-day outfits such electronic devices need to conform to requirements as regards wear-ability, this is the vision of wearable technology. Wearable systems are characterized by their capability to automatically identify the activity and the behavioral status of their wearer as well as of the situation around them, and to use this information to adjust the systems’ configuration and functionality. This write-up focused on recent developments in the field of Smart Fabrics and pays particular attention to the materials and their manufacturing techniques.